Synthesis of lauryl methacrylate and poly(ethylene glycol) methyl ether methacrylate copolymers with tunable microstructure and emulsifying properties. (July 2019) - Iborra, Agustín; Salvatierra, Lucas; Giussi, Juan M.; Azzaroni, Omar
Graphical abstract: Highlights: Controlled synthesis of amphiphilic copolymer based on LMA and PEGMA monomers. Effect of compositional drift in thermal and emulsifier properties. Interesting bulk rheological properties. Incorporation of toluene in formed micelles. Evaluation of loading capacity using 2D NMR. Abstract: In this work we study the synthesis and properties of copolymers constituted of lauryl methacrylate and poly(ethylene glycol) methyl ether methacrylate monomers, prepared by atom transfer radical copolymerization in the entire composition range (with low and high monomer conversion). We propose a description of the copolymer microstructure, and evaluate the composition drift effect in the thermal and solution properties of the obtained copolymers. Nuclear magnetic resonance (NMR) was used to determine the chemical composition of the copolymers, while differential scanning calorimetry and themogravimetric analysis was employed to understand the thermal chracteristics. Rheological studies were conducted to obtain the viscosity and viscoelastic properties that were correlated with thermal transitions at different temperatures. Finally, dynamic light scattering (DLS) and surface tension measurements were used to evaluate the copolymer solution properties. The incorporation of an oil phase in the self-assembled aggregates was evaluated by DLS and characterized by atomic force microscopy, diffusion-ordered spectroscopy NMR and nuclear Overhauser effect NMR spectroscopy. Our results suggest a longer sequence of LMA units in the copolymer chain and a drift effect in the case of high monomer conversions. A clear dependence on copolymer composition and microstructure to disperse an oil phase in water was observed. We believe that these results bring valuable knowledge that advances the field of macrosurfactants as well as their potential applications in oil recovery and other industrial processes.